Revitalizing Criminological Theory: Towards a New Ultra-Realism - Hall, Stephen (2015)
This book provides a short, comprehensive and accessible introduction to Ultra-Realism: a unique and radical school of criminological thought that has been developed by the authors over a number of years. After first outlining existing schools of thought, their major intellectual flaws and their underlying politics in a condensed guide that will be invaluable to all undergraduate and postgraduate students, Hall and Winlow introduce a number of important new concepts to criminology and suggest a new philosophical foundation, theoretical framework and research programme. These developments will enhance the discipline’s ability to explain human motivations, construct insightful representations of reality and answer the fundamental question of why some human beings risk inflicting harm on others to further their own interests or achieve various ends